(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we investigate the Cahn-Hilliard equation defined on the half space and subject to the Neumann boundary and initial condition. For given initial data in some sobolev space, we prove the existence and analytic smoothing effect of the solution.